Preoperative vaginal wash with povidone iodine solution to reduce post caesarean infectious morbidity (Texas Journal of Medical Science, 2023)
Post-operative infection is frequently seen in Caesarean section. Vaginal wash with 10% povidone iodine & Antibiotic prophylaxis may have significant impact in reduction of infections and thus the need to study their roles in sepsis prevention systematically.